Keistimewaan Bahasa Arab Sebagai bahasa al-Quran dan Kepentingan Menguasainya Bagi Para Mufassirīn: The Privilege of Arabic as the Language of the Qur'an and the Importance of Mastering It for the Mufassirīn - Ahmad H. Osman, Rahmah; Abu Hassan, Muhammad Ikram (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
Abstrak Seorang Mufassir ibarat permata bagi umat Islam. Tugasannya amat penting dalam memberikan kefahaman yang benar terhadap ayat-ayat al-Qur’an yang merupakan kalam Allah SWT. Memandangkan al-Qur’an diturunkan dalam bahasa Arab dan memahami isinya perlu kepada tadabbur dan pemerhatian, maka kajian ini meneliti salah satu aspek terpenting yang perlu dikuasai oleh seorang mufassir iaitu mengetahui dan memahami bahasa Arab. Tujuan kajian ini ialah merungkai betapa pentingnya elemen bahasa Arab bagi seorang mufassir, selanjutnya meneliti betapa besar kesan bahasa Arab dalam memahami al-Quran. Begitu juga mengenal pasti ilmu-ilmu dasar dalam cabang ilmu bahasa Arab yang perlu dikuasai oleh seorang Mufassir. Kajian ini menggunakan kaedah deskriptif dengan mengumpul pandangan ulama tafsir dan bahasa Arab silam terhadap kepentingan menguasai dan memahami bahasa arab seterusnya mengkaji dan mengeluarkan kesimpulan darinya. Kajian mendapati bahawa memahami al-Qur’an merupakan suatu tuntutan terpenting dalam syariat Islam dan tidak boleh mencapai memahami al-Qur’an melainkan dengan menguasai bahasa Arab. Selain itu, dalam memahami al-Qur’an terdapat beberapa ilmu penting yang tersenarai sebahagian besarnya di bawah cabang ilmu bahasa Arab. Di samping itu, hukum mendalami bahasa Arab merupakan Fardhu Kifayah bagi umat Islam. Abstract A Mufassir is like a jewel for Muslims. His task is very important in providing a true understanding of the verses of the Qur'an which is the word of Allah SWT. Since the Qur’an was revealed in Arabic and understanding its contents is necessary to tadabbur and observation, then this study examines one of the most important aspects that need to be mastered by a mufassir which is to know and understand the Arabic language. The purpose of this study is to dismantle the importance of the elements of the Arabic language for a mufassir, further examine the great impact of the Arabic language in understanding the Qur'an. Similarly, identify the basic knowledge in the branch of Arabic language that needs to be mastered by a commentator. This study uses a descriptive method by collecting the views of scholars of tafsir and the Arabic language of the past on the importance of mastering and understanding the Arabic language and then study and draw conclusions from it. The study found that understanding the Qur’an is one of the most important requirements in Islamic law and cannot achieve understanding of the Qur’an except by mastering the Arabic language. In addition, in understanding the Qur’an there are some important sciences that are listed largely under the branch of Arabic language. In addition, the law of learning the Arabic language is Fardhu Kifayah for Muslims.